2012
DOI: 10.1007/s00402-012-1573-9
|View full text |Cite
|
Sign up to set email alerts
|

Abductor mechanism tears in primary total hip arthroplasty

Abstract: Tears are increasingly prevalent in women of advancing years and lower socioeconomic status which should be considered when planning operative approach in this demographic. When recognised and repaired there is no difference in the clinical outcome for those with abductor mechanism tears of the hip.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 11 publications
0
32
0
5
Order By: Relevance
“…tendons in 20% of the patients 11 . Hendry et al assessed 835 patients undergoing total hip replacement and found that 25% had a gluteal tendon tear, with the greatest prevalence in elderly women 20 .…”
mentioning
confidence: 99%
“…tendons in 20% of the patients 11 . Hendry et al assessed 835 patients undergoing total hip replacement and found that 25% had a gluteal tendon tear, with the greatest prevalence in elderly women 20 .…”
mentioning
confidence: 99%
“…In the current literature, the incidence of idiopathic abductor tears in hips underoing THA using a lateral (Hardinge) approach ranges between 20% and 25.4% while the incidence using a posterolateral approach was found to be 1.6% [2][3][4][5][6]. In our study, the incidence using a posterolateral approach was 0.68%.…”
Section: Discussionmentioning
confidence: 56%
“…In our study, the incidence using a posterolateral approach was 0.68%. Hendry et al postulated that when using a posterior approach, a vast majority of low-grade tears are not repaired because they are not identified [6]. Although the single surgeon in this study carefully examined the anterior 2/3 rd of each gluteus medius tendon, the comparatively low incidence supports the hypothesis that the posterolateral approach may limit the evaluation of abductor pathology and under report its true incidence.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Abductor weakness is a particular concern after DLA THA, with a reported incidence of 4%–20% 49. It is likely caused by preoperative abductor degeneration, seen in 20.0%–25.4% of THA patients, and failed tenotomy repair 575859. DAA is presumably more “muscle friendly,” thanks to the utilization of an intermuscular interval.…”
Section: Discussionmentioning
confidence: 99%